2019
DOI: 10.3390/rs11131567
|View full text |Cite
|
Sign up to set email alerts
|

An Approach to Moho Topography Recovery Using the On-Orbit GOCE Gravity Gradients and Its Applications in Tibet

Abstract: It is significant to determine the refined Moho topography for understanding the tectonic structure of the crust and upper mantle. A novel method to invert the Moho topography from the on-orbit gravity gradients is proposed in the present study. The Moho topography of Tibet is estimated by our method, which is verified by previous studies. The research results show that: (1) the deepest Moho of Tibet, approximately 70 km, is located at the western Kunlun area, where it corresponds well to that of previous publ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 54 publications
0
5
0
Order By: Relevance
“…It is a key factor for obtaining refined crust-mantle interface depth to accurately extract the gravity anomaly signal caused by the crust-mantle interface relief, which needs to remove the effect of sediments, consolidated crystalline lunar crust and lower lunar mantle (Wan et al, 2019). The common methods for these corrections depend on existing lunar crustal and mantle models.…”
Section: Crust-mantle Interface Depth Determinationmentioning
confidence: 99%
“…It is a key factor for obtaining refined crust-mantle interface depth to accurately extract the gravity anomaly signal caused by the crust-mantle interface relief, which needs to remove the effect of sediments, consolidated crystalline lunar crust and lower lunar mantle (Wan et al, 2019). The common methods for these corrections depend on existing lunar crustal and mantle models.…”
Section: Crust-mantle Interface Depth Determinationmentioning
confidence: 99%
“…Due to the collision between the Eurasian and Indian plates, the TP has undergone complex tectonic evolution for 50 million years, and is an ideal region to study plate tectonics, continental collision, and orogeny (Molnar and Tapponnier, 1975;Tapponnier et al, 1982;Royden et al, 2008;Gao et al, 2013;Xu et al, 2017;Xu et al, 2020). The geometry and trend of the Moho discontinuity provide crucial insights for understanding these internal tectonic phenomena (Gao et al, 2013;Xu et al, 2017;Wan et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…In comparison, gravity methods can achieve high resolution models over large scales. Several scholars used gravity methods to study the Moho topography of the TP (Hao et al, 2014;Chen and Tenzer, 2017;Xu et al, 2017;Wan et al, 2019;Xuan and Jin, 2022). Hao et al (2014) calculated the crustal thickness of the TP based on the EGM2008 and CRUST 2.0 models, and found that the crustal thickness of the TP ranges from 50 to 75 km.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Reference [14] utilized the Vening Meinesz s isostatic theory to determine the Moho depth, and [15] reformulated the Moritz s problem, calling it the Vening Meinesz-Moritz (VMM) inverse problem of isostasy. The VMM model has been used extensively to determine a Moho depth globally and regionally [8,[16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%